2018
DOI: 10.1002/pbc.27395
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and accuracy of UF/NCI phantoms and Monte Carlo retrospective dosimetry in children treated on National Wilms Tumor Study protocols

Abstract: This pilot study has demonstrated that the patient-matched UF/NCI phantoms together with MC dosimetry is an accurate model for performing retrospective 3D dosimetry in large-scale epidemiology studies such as the NWTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Their utilization for potentially refining indications for RT in certain risk groups remains to be studied. Detailed studies of late toxicities specifically by analyzing the effects of RT doses to target organs is critical to improve our understanding of the relationship between RT and a variety of toxicities such as infertility, hypogonadism, congestive heart failure and secondary malignancies [60]. International collaborations like the Pediatric Normal Tissue Effects in the Clinic (PENTEC), are systematically analyzing the association between RT doses and volumes and organ toxicities by reviewing published reports of late toxicities following RT in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their utilization for potentially refining indications for RT in certain risk groups remains to be studied. Detailed studies of late toxicities specifically by analyzing the effects of RT doses to target organs is critical to improve our understanding of the relationship between RT and a variety of toxicities such as infertility, hypogonadism, congestive heart failure and secondary malignancies [60]. International collaborations like the Pediatric Normal Tissue Effects in the Clinic (PENTEC), are systematically analyzing the association between RT doses and volumes and organ toxicities by reviewing published reports of late toxicities following RT in children.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach, as used by the CCSS, is to perform retrospective dosimetry using patient age and sex-matched phantoms to recreate multiorgan dosimetry from past treatments for correlation with late toxicities [61]. A similar approach using patientmatched 3D University of Florida/National Cancer Institute (UF/NCI) phantoms is currently being completed by the NWTS Late Effects Study [60]. A better understanding of the RT dose thresholds for these toxicities will help promote the adoption of interventions for their prevention and mitigation.…”
Section: Discussionmentioning
confidence: 99%
“…After processing the phantoms in the DICOM-RT Generator, the resulting DICOM-RT files were imported into the Philips Pinnacle TPS at Northwestern University, where patientspecific RT fields were then reconstructed (including photon energy, field-type, and prescribed dose) based on scanned paper medical records available from the NWTS database (Kalapurakal et al 2018). These radiotherapy plans were created by a practicing radiation oncologist and senior medical physicist who carefully reviewed the available medical records and portal films.…”
Section: National Wilms Tumor Study (Nwts) Application-using the Dicom-rtmentioning
confidence: 99%
“…8,[12][13][14][15] These methods provide 3-D dose estimations by emulating the historical treatment on a 3-D patient-resembling surrogate anatomy, e.g., physical phantoms, 12 computational phantoms, 8,12,15 or surrogate CTs. 12,14,16 For a dose reconstruction approach, the discrepancy between the surrogate anatomy and the true anatomy of the patient for whom the plan was originally designed is one of the main sources of uncertainties, making it an important topic to research. 7,8,17 As variations in anatomy exist in the population, it has been found that an approach that uses a representative surrogate patient's anatomy to reconstruct RT dose for an individual patient can introduce large dose uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…The last step, i.e., the dose calculation, can be automated, by scripting the dose calculation algorithms in a commercial treatment planning system (TPS), or using other standalone analytical or Monte-Carlo dose calculation algorithms. 15,16,28 The bottleneck that prevents performing dose reconstruction on a large scale is the intermediate step of RT plan emulation (step 2).…”
Section: Introductionmentioning
confidence: 99%